Zingiber Zerumbet : Pharmacological Values of Zerumbone and the Extraction Technology Evolution - Nurul 'Uyun Ahmad; Mariam Firdhaus Mad Nordin; Norrashidah Mokhtar; Izzati Mohamad Abdul Wahab; Mardawani Mohamad; Tan Ka Liong; Siti Nur Khairunisa Mohd Amir (Penerbit UTM, 2024)
Indexed by WOS/Scopus/ERA/MyCite